2023
DOI: 10.3389/fphar.2023.1115226
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 15 in liver diseases: Insights into metabolic reprogramming

Abstract: Liver diseases, characterized by metabolic disorder, have become a global public health problem with high morbidity and mortality. Krüppel-like factor 15 (KLF15) is a zinc-finger transcription factor mainly enriched in liver. Increasing evidence suggests that hepatic KLF15 is activated rapidly during fasting, and contributes to the regulation of gluconeogenesis, lipid, amino acid catabolism, bile acids, endobiotic and xenobiotic metabolism. This review summarizes the latest advances of KLF15 in metabolic repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 95 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…The significant decrease in the levels of BCAA pathway enzymes in FLC suggested that their transcription may be reduced. Krüppel-like factor 15 (KLF15) is an important transcriptional regulator of metabolic gene expression in the liver, including BCAA catabolism and urea cycle genes 31,50,51 . To investigate whether KLF15 plays a role in FLC metabolism, we first probed for KLF15 in lysates from FLC patients by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…The significant decrease in the levels of BCAA pathway enzymes in FLC suggested that their transcription may be reduced. Krüppel-like factor 15 (KLF15) is an important transcriptional regulator of metabolic gene expression in the liver, including BCAA catabolism and urea cycle genes 31,50,51 . To investigate whether KLF15 plays a role in FLC metabolism, we first probed for KLF15 in lysates from FLC patients by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, studies have identified KLF15 as a crucial regulator of metabolism [45], showing that KLF15 enhances bile acid production in the liver, leading to increased nutrient uptake [46]. This suggests that KLF15 may emerge as a major therapeutic target for bile-acid-related metabolic diseases [47]. A study implicates HNF4A as the top upstream regulator of metabolism in liver cancer, particularly in a subtype of cholangiocarcinoma with high HNF4A and genes related to bile acid metabolism [48].…”
Section: Discussionmentioning
confidence: 99%